Emergence of Meropenem Resistance Among Cefotaxime Non-susceptible Streptococcus pneumoniae: Evidence and Challenges - Varghese, Rosemol; Basu, Soumya; Neeravi, Ayyanraj; Pragasam, Agilakumari; Aravind, V.; Gupta, Richa; Miraclin, Angel; Ramaiah, Sudha; Anbarasu, Anand; Veeraraghavan, Balaji (Frontiers in Microbiology, 2022)
The principal causative agent of Acute Bacterial Meningitis (ABM) in children and the elderly is S. pneumoniae, with a widespread increase in penicillin resistance. Resistance is due to non-synonymous single nucleotide polymorphisms (nsSNPs) that alter the penicillin-binding proteins (PBPs), the targets for all β-lactam drugs. Hence, resistance against one β-lactam antibiotic may positively select another. Since meropenem is an alternative to cefotaxime in meningeal infections, we aim to identify whether nsSNPs in the PBPs causing penicillin and cefotaxime resistance can decrease the pneumococcal susceptibility to meropenem. Comparison of the nsSNPs in the PBPs between the cefotaxime resistant Indian (n=33) and global isolates (n=28) revealed that nsSNPs in PBP1A alone elevated meropenem MICs to 0.12 µg/ml, and nsSNPs in both PBP2X and 2B combined with PBP1A increases MIC to ≥ 0.25 µg/ml. Molecular docking confirmed the decrease in the PBP- drug binding affinity due to the nsSNPs, thereby increasing the inhibition potential and the MIC values, leading to resistance. Structural dynamics and thermodynamic stability pattern in PBPs as a result of mutations further depicted that the accumulation of certain nsSNPs in the functional domains reduced the drug affinity without majorly affecting the overall stability of the proteins. Restricting meropenem usage and promoting combination therapy with antibiotics having non-PBPs as targets to treat cefotaxime nonsusceptible S. pneumoniae meningitis can prevent the selection of β-lactam resistance.